Pembangunan WhatsApp Chatbot sebagai layanan kecerdasan buatan di Perpustakaan UIN Walisongo Semarang - Muh Ahlis Ahwan; Nutfatin Abiadhoh; Alan Budi Kusuma; Umar Falahul Alam (Perpustakaan Universitas Gadjah Mada, 2024)
Introduction. This research aims to explore WhatsApp Chatbot as an artificial intelligence service at the UIN Walisongo Library. Data Collection Methods. The method used is R&D with the Waterfall model from Roger S. Pressman starting from the stages of communication, planning, modeling, construction, to deployment. To build a WhatsApp Chatbot system dialog, data collection processes were conducted using observations, interviews, questionnaires and documentation. Data Analysis. The data was analyzed using descriptive qualitative. Further, the validity of the data was tested by triangulation of sources and techniques. Results and Discussion. WhatsApp Chatbot at UIN Walisongo Library was developed in five stages. They are communicating, planning, modeling, manufacturing and deploying. Information mapping is devided into Admin, Member, and General levels. WhatsApp Chatbot is integrated with SLiMS to produce dynamic and static answer obtained from librarian responses. Conclusion. WhatsApp Chatbot becomes a solution for librarians and an alternative for library users at UIN Walisongo Library. It is expected that the WhatsApp Chatbot can also be integrated with other systems in the library so that integrated information can provide more complete information to meet the needs of library users.